The Limits of Knowledge and the Limits of Science - Bermejo Barrera, José Carlos (USC Editora, 2013)
This is an essay on the possibility and limits of knowledge, in general, and scientific knowledge, in particular. In Chapter 1 the postulates of Kantian critical philosophy are broadened to make contact with modern cognitive theories; it is argued that all knowledge should be regarded as an exclusively human product rather than the work of a transcendental being. On this basis the fundamental question posed in this text concerns the limits of knowledge defined by the limitations of instruments of observation, classificationn and analysis, and the limitations of researchers as individuals and as scientific communities. In this last respect, it is argued that current systems for the production and dissemination of scientific knowledge, while making such knowledgem while making such knowledge possible, also favour its sterility. Two specific areas of science are analysed from these points of view: psychiatry and standard cosmology.